1993
DOI: 10.1038/jcbfm.1993.69
|View full text |Cite
|
Sign up to set email alerts
|

Local Cerebral Blood Flow in Rats with Congenital Hydrocephalus

Abstract: Local cerebral blood flow (LCBF) has been measured by [14C]iodoantipyrine quantitative autoradiography in H-Tx rats with inherited congenital hydrocephalus at 10, 21, and 30 days after birth. LCBF at 10 days was uniformly low in all ten brain regions studied and not significantly different between hydrocephalic and age-matched control rats. By 21 days LCBF had increased significantly in control rats. LCBF was significantly lower (<69%) in the hydrocephalics in all cortical regions and in the inferior collic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 29 publications
4
20
0
Order By: Relevance
“…A diffusely, but only moderately increased production of lactate, as a consequence of global, mild ischemia, would be in accordance with the finding of a reduced cerebral blood flow (7)(8)(9)(10) and metabolic changes (8,11) in both gray and white matter areas in other models of experimental hydrocephalus. Diffusion of lactate toward the ventricles, followed by accumulation within the noncommunicating pool of CSF, would then explain the increase in CSF lactate levels.…”
Section: The Localization Of Lactatesupporting
confidence: 67%
“…A diffusely, but only moderately increased production of lactate, as a consequence of global, mild ischemia, would be in accordance with the finding of a reduced cerebral blood flow (7)(8)(9)(10) and metabolic changes (8,11) in both gray and white matter areas in other models of experimental hydrocephalus. Diffusion of lactate toward the ventricles, followed by accumulation within the noncommunicating pool of CSF, would then explain the increase in CSF lactate levels.…”
Section: The Localization Of Lactatesupporting
confidence: 67%
“…Presumably, the decline in CPP was primarily responsible for the observed decreases in CBF in the three brain regions, as documented by radioactively labeled microspheres. Decreased CBF has been observed in a variety of experimental models of hydrocephalus (2)(3)(4).…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations NIRS, near-infrared spectroscopy HbO 2 , oxygenated Hb Hb, deoxygenated Hb HbD, Hb difference signal HbT, total Hb CytOx, oxidized cytochrome aa 3 ICP, intracranial pressure MAP, mean arterial pressure CPP, cerebral perfusion pressure CBF, cerebral blood flow rCBF, regional cerebral blood flow dpf, differential path-length factor Rational management of infantile hydrocephalus requires information about the disturbances in cerebral perfusion and metabolism that may contribute to the development of brain injury. Substantial evidence indicates that impairments of cerebral perfusion and metabolism play a role in the pathogenesis of brain injury secondary to hydrocephalus (1)(2)(3)(4)(5)(6)(7)(8). However, currently there are major limitations in the ability to define changes in cerebral hemodynamics and metabolism quantitatively, continuously, and noninvasively at the bedside of the human infant.…”
mentioning
confidence: 99%
“…Prior studies have shown reduced CBF with elevated ICP in various animal models of hydrocephalus. [17][18][19][20] Reduced CBF has also been reported in small case series of children with either congenital hydrocephalus or acute hydrocephalus from brain tumors by using 15 O-PET 21 or SPECT. 22 Recently, 2D phase-contrast MRA has shown that carotid and basilar arterial flow rates are reduced in infants with hydrocephalus.…”
mentioning
confidence: 99%